Molecular Confirmation of Ranavirus Infection in Amphibians From Chad, Africa - Box, Erin K.; Cleveland, Christopher A.; Subramaniam, Kuttichantran; Waltzek, Thomas B.; Yabsley, Michael J. (Frontiers in Veterinary Science, 2021)
Ranaviruses are DNA viruses (Family Iridoviridae; Subfamily Alphairidovirinae) and ranaviral disease is considered an emerging infectious disease of ectothermic vertebrates. Ranavirus infection can have varying pathological effects on infected amphibians, reptiles, and fish, most notably causing significant mortality events and population declines. Despite having a broad global range with reports from 6 continents, only a single incidental finding in Xenopus longipes from mainland Africa (Cameroon) is known and lacks molecular confirmation. Thus, there is a considerable knowledge gap concerning ranaviruses in Africa. We opportunistically obtained tissue samples from 160 amphibians representing 5 genera (Hoplobatrachus, Hylarana, Ptychadena, Pyxicephalus, and Xenopus) and 2 turtles (Pelomedusa sp.) from Chad, Africa. Samples were tested for ranavirus infection using a conventional PCR assay targeting the major capsid protein (MCP). A total of 25/160 (16%) frogs tested positive including 15/87 (17%) Hoplobatrachus occipitalis, 10/58 (17%) Ptychadena spp., 0/3 Pyxicephalus spp., 0/9 Xenopus spp., and 0/3 Hylarana spp. One of two turtles tested positive. Partial MCP gene sequences indicated all samples were >98% similar to several frog virus 3 (FV3)-like sequences. Additional gene targets (DNA polymerase [DNApol], ribonucleotide reductase alpha [RNR- α], ribonucleotide reductase beta subunit [RNR- β]) were sequenced to provide further detailed classification of the virus. Sequences of individual gene targets indicate that the ranavirus detected in frogs in Chad is most similar to tiger frog virus (TFV), a FV3-like virus previously isolated from diseased amphibians cultured in China and Thailand. Full genome sequencing of one sample indicates that the Chad frog virus (CFV) is a well-supported sister group to the TFVs previously determined from Asia. This work represents the first molecular confirmation of ranaviruses from Africa and is a first step in comparing ranavirus phylogeography on a local and global scale.